Нашарованість однієї метафори. Голос та сльози як axis mundi - Пандуревич, Є. (Народна творчість та етнологія, 2012)
In this paper, the focus is on the archaic magic formula related to voice and tears, viewed in the context of a ritual connection between heaven and earth by building a symbolic Cosmic axis (axis mundi). Since there is already formed recognizable narrative nucleus in conjuration texts, to which it is primarily associated, we followed the way to the constitution of the oral poetic formula by observing a number of different syuzhet models incorporating the theme of «great weeping» as a stylized form of the phrase «voice to the sky, tear to the soil» which, in a specific way, works in texts of simple forms. The basic semantic core (one’s sense of vulnerability and need to be mediated by higher powers to overcome it) remained preserved despite the high degree of stylization, and its release and reception depend on the intention of the genre and, above all, the cultural context that prevailed at that time.